Jia-Wei-Kai-Xin-San, an Herbal Medicine Formula, Ameliorates Cognitive Deficits via Modulating Metabolism of Beta Amyloid Protein and Neurotrophic Factors in Hippocampus of Aβ1-42 Induced Cognitive Deficit Mice - Zhu, Yue; Shi, Yiwei; Cao, Cheng; Han, Zhenxiang; Liu, Mengqiu; Qi, Mingzhu; Huang, Renjie; Zhu, Ziqiang; Qian, Dawei; Duan, Jin-ao (Frontiers in Pharmacology, 2019)
Jia-Wei-Kai-Xin-San (JWKXS) is a Chinese medicine formula applied for treating morbid forgetfulness in ancient China. Today, this formula is frequently applied for Alzheimer’s disease and vascular dementia (VD) in clinic. Here, we developed it as granules and aimed to evaluate its anti-AD effect on amyloid protein 1-42 (A1-42) induced cognitive deficit mice and reveal the possible molecular mechanisms. Firstly, daily intra-gastric administration of chemically standardized of JWKXS granules for seven days significantly ameliorated the cognitive deficit symptoms and inhibited cell apoptosis in hippocampus on A1-42 injection mice according by Morris water maze test. In hippocampus of model mice, JWKXS granules significantly decreased Alevel, increased SOD activity and decreased MDA level in hippocampus of model mice. It also restored acetylcholine amounts, inhibited acetylcholinesterase activities and increased choline acetyltransferase activities. In addition, JWKXS granules enablesd the transformation of precursors of NGF and BDNF into mature forms. Furthermore, JWKXS granules could regulate gene expressions related to A production, transportation, degradation and neurotrophic factor transformation, which led to down-regulation of Aand up-regulation of NGF and BDNF. These findings suggested that JWKXS granules might ameliorated cognitive deficit effect via decreasing A levelsdeposits, protecting neuron from oxidation damages and nourishing neuron nourishment, which could serve as alternative medicine for patients suffering from AD.